Rebuilding Tazo Traditional House East Nusa Tenggara by Excavating Collective Memories - Khambali, Mohammad Resha; Lukito, Yulia Nurliani (University of Merdeka Malang, 2022)
Traditional life in Indonesia is significantly related to spoken culture from the older generation to the young age. This condition unconsciously shows a risk of void space when there is a disconnected generation. Only a small number of written documentation and drawings exist for Vernacular Architecture in Indonesia or Architecture Nusantara. Tazo is one of several villages in Riung district, Flores island, in Nusa Tenggara Timur province, Indonesia. The current condition of the traditional house of Tazo is extinct, and there are no physical traces anymore. In this paper, we will show the excavation of the traditional house of the Tazo with the method of searching for data through oral interviews with existing traditional elders who have experienced living in their traditional house before. Step by step, the shape of this traditional house is illustrated architecturally and can be recognized again by the memory of the traditional elders of Kampung Tazo.